PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA NON FISIK, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT Sukses Abadi Engineering Jababeka Cikarang Utara) - Muhammad Nadhif Akmal Mumtaz (2022)
This study is a quantitative study that aims to determine whether there is an influence of work discipline, non-physical work environment, and leadership style on the performance of PT Sukses Abadi Engineering employees. This study used 50 respondents, the sampling technique used a saturated sampling technique. The hypothesis in this study is to determine the effect either partially or simultaneously of the variables X and Y, so that the tests used are the coefficient of determination test, f test and t test. Furthermore, the results obtained are: (1) work discipline has a positive and significant effect on employee performance, (2) non-physical work environment has a positive and significant effect on employee performance, (3) leadership style has a positive effect. and have a significant impact on employee performance. important. significant with employee performance, (4) work discipline, non-physical work environment and leadership style have a significant effect on the performance of employees of PT Sukses Abadi Engineering.